“All that remains is a diploma”: employability, policy-induced mismatch and school-to-work transitions in health vocational education - Nihan Demirkasımoğlu; Hüseyi̇n Sezer (Education + Training, 2026)
Purpose This study examines how students in health vocational high schools (HVHS) in Türkiye perceive their employability, anticipated school-to-work transitions and developing professional identities within the post-2014 qualification structure. Design/methodology/approach Drawing on career construction theory and policy feedback theory, the study adopts a qualitative case study design based on semi-structured interviews with students across two HVHS. Findings The findings reveal an education–employment mismatch manifested in four interrelated patterns: externally driven school choice, inherited expectations and post-reform disappointment, perceived misalignment between vocational training and post-graduation opportunities, and the psychosocial cost of policy change. Practical implications The findings contribute to international debates on vocationalism, youth employability and school-to-work transitions by highlighting the psychosocial and identity-related consequences of policy-induced educational mismatch. By showing how students associate perceived constraints on employability and progression with uncertainty, disappointment and identity strain, the study highlights the broader social costs of misaligned vocational education reforms. Originality/value The study demonstrates how students interpret the misalignment between a restructured vocational qualification and historically inherited occupational expectations as weakening their employability and future career prospects.